Exploring Organic Food Consumption Demand in Casual Dining Restaurants in Western Province of Sri Lanka; From the Restaurant Managers’ Perspective - Hasini Nimasha Jayawardena; Watte Gedara Shamila Rasanjani Wijesundara; Herath Mudiyanselage Jayathree Pradeepamali Herath (Cita Konsultindo Research Center, 2022)
Food tourism embraces food cultures and the niche market for organic foods grown using carbonic fertilizers, is explored in the study. But, contradictory ideas exist in literature regarding organic and conventional food consumption in Sri Lankan urban areas. Further, adaptation of organic food culture has limited researches from restaurateurs’ perspective. Therefore, the objectives were set to identify demand for organic food consumption in restaurants, examine promotional strategies used for organic foods, and finally to identify limitations of promoting organic foods. The population was registered restaurants under the Sri Lanka Tourism Development Authority (SLTDA) and 28 restaurant managers from casual dining restaurants in the Western Province of Sri Lanka were selected as the sample applying purposive sampling method. Primary data were collected through semi-structured interviews and analysed through content analysis method. The results emphasized that there is a positive demand from the consumers for organic food consumption when they dine-in, yet the availability of the raw materials are lacking in the industry. Therefore, the study recommends government involvement in policymaking to strengthen organic supply chains and in developing a sustainable restaurant industry in Sri Lanka. Keywords: